Fragiles but Resilient. The Key Strategies to Cope with Pandemic in Persons with Multiple Sclerosis. A Controlled Web Survey - Annalisa, Sgoifo; Michele, Nichelatti; Maria, Raffaella Marazzi; Emanuela, Laura Susani; Lorenzo, Saraceno; Maria, Grazia Esposito; Concetta, Campagna; Elio, Agostoni; Alessandra, Protti (Journal of Neurological Research And Therapy, 2022)
Background SARS-CoV-2 pandemic represented an unexpected psychological stress, being a major threat to health and limiting daily’s life, especially for the fragile population. How could the people with (pw) Multiple Sclerosis (MS) cope with this emergency? Objective To observe the pwMS’s psychological reaction in comparison with non affected persons and to evaluate the impact of lifestyle changes on psychological symptoms, due to the pandemic. Methods The study was observational, retrospective, controlled, focused on good clinical practice and conducted at Niguarda Hospital. PwMS and controls filled a web survey containing anamnestic data, habits, depression and anxiety self-questionnaires. The primary outcome was the pwMS’s psychological anxiety and depression score compared with controls. Results On April, 10 2020, 88/165 pwMS and 187 controls joined the study. Unexpectedly, no significant differences between groups were observed for depression mean score: 6.6(5.2) in pwMS and 6.2(4.8) in controls and for anxiety: 5.9(4.8) and 5.0(4.2). PwMS focused on health concern more often than controls, but they respected the restrictions more easily and benefited from practical activities more than controls. Conclusion PwMS showed a proper psychological resilience in comparison with controls. These findings might guide the clinical interviews and suggest both the areas to be supported and the strengths to be promoted in pwMS.
Keywords: Anxiety; depression; Multiple sclerosis; SARS-CoV-2 pandemic; resilience